2018
DOI: 10.3390/medicines5010004
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Chronic Toxicity of the Hydroethanolic Leaf Extract of Telfairia occidentalis Hook. f. (Cucurbitaceae) in Male Rats

Abstract: Background: Due to its nutritional and medicinal values, the leaf of Telfairia occidentalis Hook f. (Cucurbitaceae) is consumed in different parts of Nigeria. Acute and sub-chronic toxicity of the hydroethanolic leaf extract of Telfairia occidentalis were investigated in this study. Methods: Sixty-four male rats were randomized into four different groups of 16 animals each and were separately administered 80, 400 and 2000 mg/kg T. occidentalis orally (p.o.) for 60 days. Animals were sacrificed and blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Serum urea accumulation is used as the acute marker, while serum creatinine accumulation is used in detecting renal toxicity. 2 In this study, the oral administration of P. senegalensis extract showed a significant (p ≤ 0.05) increase in creatinine levels at the dose of 600 mg/kg of the extract (Table 3) indicating signs of chronic renal toxicity with increase in dose of the extract. The histological section of the rat kidneys showed a dose-dependent glomerular and tubular necrosis ( Figure 2).…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Serum urea accumulation is used as the acute marker, while serum creatinine accumulation is used in detecting renal toxicity. 2 In this study, the oral administration of P. senegalensis extract showed a significant (p ≤ 0.05) increase in creatinine levels at the dose of 600 mg/kg of the extract (Table 3) indicating signs of chronic renal toxicity with increase in dose of the extract. The histological section of the rat kidneys showed a dose-dependent glomerular and tubular necrosis ( Figure 2).…”
Section: Resultssupporting
confidence: 48%
“…These factors include hepatic toxicity of the main constituents and contamination of preparations by heavy metals or microorganisms. 2 The goals of toxicity testing are to identify possible adverse effects of exposure to environmental agents, to develop doseresponse relationships that can elucidate the severity of effects associated with known exposures, and ultimately to predict the effects of exposure of human populations. 3 Pavonia senegalensis (Cav.)…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates with the findings of Akubue et al (1980) who reported venous congestion and in some cases burst vessels in the liver, spleen, lungs and heart of rats given aqueous extract of Telfairia occidentalis while Iweala and Obioda (2009) also reported irregularities in the liver of rats fed Telfairia occidentalis supplemented diet. Acute toxicity including hepatic toxicity have been reported (Akindele et al, 2018;Imosemi, 2018) in mice given Telfairia occidentalis up to 5000 mg/kg orally, with signs of decreased locomotion, calmness, writhing and increased breathing at higher doses of LD50 of intraperitoneal administration at 3000-5000 mg/kg. Although, there were no lesion observed in the testes in all the treatments, cocks on treatments E and F (120 and 150 mL TOLE/L) showed reduced germinal epithelium height and marked sloughing of the germinal epithelium respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Herbal preparations currently serve the health needs, and there is clear evidence of the therapeutic benefits they have attained widespread acceptability as therapeutic agents 2,3 . It is a widely held belief that herbal preparations are safe.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the belief and claim of being natural and safe, herbal remedies have been associated with lethal effects, which have been attributed to several factors. These factors include hepatic toxicity of the main constituents and contamination of preparations by heavy metals or microorganisms 3 .…”
Section: Introductionmentioning
confidence: 99%